The synthesis of near-infrared reflective brown ceramic pigment of Zn1-xMgxFe2O4 - Rakkwamsuk, Pattana; Supothina, Sitthisuntorn; Pansukhumthana, Lada; Tangkittimasak, Teerasak (Bulletin of Applied Sciences, 2022)
This paper presents the research and development of brown ceramic pigment synthesized by solid-state reaction of Zinc Ferrite doped with magnesium oxide that formed complex inorganic compound pigment (CICP) of Zn1-xMgxFe2O4. The pigment offered shades of brown and high reflectivity in the near-infrared (NIR) region. The pigment can be used as a vehicle for a high solar reflective coating that reduces heat absorbed by building structures, promotes energy conservation in an air-conditioning system, and enhance human thermal comfort in the building. The synthesis was performed by ball-milling raw materials composed of ZnO, Fe2O3 and MgO at various compositions to reactively form Zn1-xMgxFe2O4 in the calcination process at 1,000, 1,100 and 1,200 °C, where x was varied between 0 and 1. The calcined compound was then washed, oven-dried and ground, that yielded powdered pigment with the shade of brown. The color of pigment, measured and computed in compliance with CIE L* a* b*, did not alter as the calcining temperature changed but varied significantly with x. As x increased, the color changed from brown to red brown. The brown pigment possessed high solar reflectance in the NIR region. Its reflectance increased with x. It was found that the pigment synthesized with x = 0.8, Zn0.2Mg0.8Fe2O4, and calcined at 1,000 °C offered the highest NIR reflectance at 72.9 %